2014
DOI: 10.1017/s0305000914000257
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension asymmetries in language acquisition: a test for Relativized Minimality

Abstract: A B S T R A C TCross-linguistic studies have shown that typically developing children have difficulties comprehending non-canonical structures. These findings have been interpreted within the Relativized Minimality (RM) approach, according to which local relations cannot be established between two terms of a dependency if an intervening element possesses similar morphosyntactic features. In an extension of RM, Friedmann, Belletti, and Rizzi () suggested that lexical NP restriction is the source of minimali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…Any effect of relativized minimality therefore must be visible as an interaction with argument type: for example, a difference between the two object questions, but no corresponding difference between the subject questions. The features that have been implicated in relativized minimality in other studies are NP (Friedmann et al, 2009), case (Arosio, Guasti, & Stucchi, 2011; Arosio, Yatsushiro, et al, 2011; Guasti, Stavrakaki, & Arosio, 2012; Varlokosta et al, 2015), number (Adani et al, 2010), and gender (Adani et al, 2010). In our study, gender was not tested, 7 but the features NP, case, and (indirectly) number were relevant.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Any effect of relativized minimality therefore must be visible as an interaction with argument type: for example, a difference between the two object questions, but no corresponding difference between the subject questions. The features that have been implicated in relativized minimality in other studies are NP (Friedmann et al, 2009), case (Arosio, Guasti, & Stucchi, 2011; Arosio, Yatsushiro, et al, 2011; Guasti, Stavrakaki, & Arosio, 2012; Varlokosta et al, 2015), number (Adani et al, 2010), and gender (Adani et al, 2010). In our study, gender was not tested, 7 but the features NP, case, and (indirectly) number were relevant.…”
Section: Discussionmentioning
confidence: 91%
“…Serbian differs in two ways from English: Case marking on the initial interrogative pronoun (and also on the other noun phrase in the sentence) distinguishes between the subject and object questions, while the word order of the verb and the other argument does not. Some work has already shown that different disambiguating factors affect children's performance differently (Adani et al, 2010;Arosio, Yatsushiro, Forgiarini, & Guasti, 2011;Guasti, Stavrakaki, & Arosio, 2012;Varlokosta et al, 2015), but no study has yet compared more than two languages. Our study is also of practical importance for the diagnosis of atypical child language in Europe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-referential object wh-questions with ti ("what") are productively used by children before age 2 (Stephany 1997;Tsimpli 2005). A comprehension study with children aged 4;0 to 5;4 found adult-like comprehension of these wh-questions (97% accuracy, Varlokosta et al 2015); we take the ceiling performance to suggest that mastery occurs already by age 4. Referential object wh-questions, i.e., which-questions, are unattested in early production (Stephany 1997;Tsimpli 2005) and are still difficult in comprehension for four-to five-year-old children (76% accuracy, Varlokosta et al 2015).…”
mentioning
confidence: 88%
“…, Varlokosta et al . ). These difficulties have been linked to the immaturity of the developing processing system e.g.…”
Section: Discussionmentioning
confidence: 97%